Cutaneous attributes of chlorogenic acid, apigenin, kaempferol and naringenin established by HPLC-TBARS-EVSC protocol and Laser Doppler flowmetry - Ruscinc, Nadia (2024)
The integumentary system, a vital organ for organisms, constitutes a multifaceted barrier against pathogens and environmental factors, crucial for maintaining homeostasis. Skin, composed of epidermis, dermis, and hypodermis, plays a pivotal role in preserving life. Intrinsic and extrinsic factors can accelerate skin aging and compromise its homeostatic functions. Solar radiation, particularly ultraviolet (UV) radiation, poses a significant risk for skin cancer and accelerates photoaging. This study explores the in vitro safety and protective effects of polyphenols (chlorogenic acid, apigenin, kaempferol, and naringenin) against UV-induced lipid peroxidation using innovative methodologies, including HET-CAM assay, HPLC-TBARS-EVSC, and laser Doppler flowmetry. The HET-CAM assay confirmed non-irritating profiles for the polyphenols. HPLC-TBARS-EVSC revealed that only naringenin exhibited a significant reduction in lipid peroxidation, while others showed pro-oxidant tendencies. Laser Doppler flowmetry demonstrated anti-inflammatory potential, with naringenin displaying superior efficacy in reducing inflammatory response induced by methyl nicotinate. This comprehensive investigation underscores the diverse protective roles of polyphenols in skin health, emphasizing naringenin\'s notable anti-radical and antiinflammatory properties.